Comparative analysis of ephemeral river ecosystem services in agricultural and natural landscapes in Mediterranean environments. A Practical Approach to Caia River - Castanho, Rui (2018)
Comparative analysis of ephemeral river ecosystem services in agricultural and natural landscapes in Mediterranean environments. A Practical Approach to Caia River. A comparison study between agricultural and natural Mediterranean environments landscapes.